Autophagy and diabetes - Milan Obradovic; Sonja Zafirovic; Zoran Gluvic; Jelena Radovanovic; Esma R. Isenovic (Open Exploration Publishing Inc., 2023)
The current literature findings on autophagy's beneficial and detrimental roles in diabetes mellitus (DM) and diabetes-related comorbidities were reviewed. The effects of oral hypoglycaemic medicines and autophagy in DM. Autophagy plays an important function in cellular homeostasis by promoting cell survival or initiating cell death in physiological settings was also assessed. Although autophagy protects insulin-target tissues, organelle failure caused by autophagy malfunction influences DM and other metabolic diseases. Endoplasmic reticulum and oxidative stress enhance autophagy levels, making it easier to regulate stress-induced intracellular changes. Evidence suggests that autophagy-caused cell death can occur when autophagy is overstimulated and constitutively activated, which might prevent or develop DM. Even though the precise role of autophagy in DM complications is uncertain, deregulation of the autophagic machinery is strongly linked to beta cell destruction and the aetiology of DM. Thus, improving autophagy dysfunction is a possible therapeutic objective in treating DM and other metabolic disorders.